Scope freezing and object shift in Ukrainian: Does Superiority matter?. (9th February 2022) - Antonyuk, Svitlana; Mykhaylyk, Roksolana
Abstract: This remark presents novel evidence on Ukrainian specificity‐inducing object shift in its interaction with quantifier scope, evidence suggesting a generalization that whatever scope interpretations are established in the postverbal field will carry over into the preverbal field. We point out that the data present a serious challenge to the Superiority account of scope freezing, since that account predicts that object shift of a QP will always freeze scope with respect to another object QP, contrary to fact. Furthermore, while Ukrainian object shift does not obey Holmberg's Generalization, we argue that it is nevertheless fully comparable to Scandinavian object shift. We propose to account for the data with a modified version of cyclic linearization . Cyclic linearization accounts for the crosslinguistic differences with respect to object shift and also derives the peculiar object shift–QP scope interaction patterns we observe, which remain obscure on the Superiority account of scope freezing.